The impact of high fructose corn syrup on liver injury and glucose metabolism: a systematic review - Yu, Zane Z.; Varahala, Sneha; Lim, Sean L. C.; Marenah, Maimuna C.; Wattacheril, Julia (Frontiers in Nutrition, 2025)
BackgroundHigh fructose corn syrup (HFCS) is a dietary sweetener that is used in a substantial portion of food and beverages. Recent evidence has cited dietary HFCS as a risk factor in the development of obesity, metabolic syndrome, and liver disease. This systematic review provides a new evaluation of the potential hepatic and metabolic risks posed by HFCS to inform both clinical practice and public health policy.MethodsWe conducted a systematic review of English-language, human studies of adults (≥18 years) with low to no alcohol intake using Covidence. Only quantitative studies that specified a link supported by direct evidence between HFCS and markers of liver injury or glucose metabolism in the setting of MASLD or NAFLD were included.ResultsThe literature search yielded 23,006 studies. After removing duplicates, 16,955 studies were screened and 16,930 were excluded after abstract screening. 20 texts were reviewed in full; 19 were excluded. 1 study was included after study selection.ConclusionThis review identifies and critically appraises the methodological strengths and limitations of the sole study meeting eligibility criteria. The 2022 study by Sigala et al. involved a non-randomized, controlled dietary intervention examining the dose–response effects of high-fructose corn syrup (HFCS) on hepatic lipid accumulation and insulin sensitivity in healthy adults. The identification of only a single eligible study emphasizes a stark absence of focused investigations in this area. Given the increasingly widespread consumption of HFCS and its prevalence in the modern food supply, this scarcity of research is concerning. Further research in this area should focus on clinical studies of longer duration, comparative studies of HFCS and other sugars, and incorporate greater demographic and geographic diversity.